2017
DOI: 10.1248/bpb.b16-00686
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of <i>SLCO1B1</i> and <i>CYP3A4/5</i> Polymorphisms on the Pharmacokinetics and Pharmacodynamics of Ticagrelor in Healthy Chinese Male Subjects

Abstract: Ticagrelor is a direct-acting P2Y12 receptor antagonist. It is rapidly absorbed and partly metabolized to the active metabolite AR-C124910XX by CYP3A4 and CYP3A5. Three genetic loci (SLCO1B1, CYP3A4, and UGT2B7) were reported to affect ticagrelor pharmacokinetics. This study aimed to investigate the possible effects of SLCO1B1 and CYP3A4/5 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of ticagrelor in healthy Chinese male volunteers. Eighteen healthy male volunteers who participated in pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…This suggests that CYP3A5 is not essential in the metabolism of ticagrelor, at least when CYP3A4 activity is normal. These results are in accordance with a recent study in which the CYP3A5*3 allele did not affect ticagrelor pharmacokinetics or pharmacodynamics in 18 healthy Chinese volunteers …”
Section: Discussionsupporting
confidence: 93%
“…This suggests that CYP3A5 is not essential in the metabolism of ticagrelor, at least when CYP3A4 activity is normal. These results are in accordance with a recent study in which the CYP3A5*3 allele did not affect ticagrelor pharmacokinetics or pharmacodynamics in 18 healthy Chinese volunteers …”
Section: Discussionsupporting
confidence: 93%
“…Ticagrelor is a P2Y 12 inhibitor that acts directly on platelets, and its efficacy is hardly affected by CYP2C19 gene polymorphisms (Wallentin et al, 2010;Li et al, 2017). The PLATO trial confirmed that ticagrelor is superior to clopidogrel in reducing adverse cardiovascular events in patients with ACS (Wallentin et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…However, these variants had no associations with cardiovascular death, MI, stroke, noncoronary artery bypass grafting-related bleeds or dyspnea [22]. It is worth noting that SLCO1B1 rs113681054 and rs4149056, CYP3A4 rs2242480 and CYP3A5 rs776746 had no significant future science group Ticagrelor pharmacogenomics Research Article effect on pharmacokinetics and pharmacodynamics of ticagrelor [23]. Thus, currently there are no genetic polymorphisms identified which may explain the antiplatelet activity of ticagrelor.…”
mentioning
confidence: 99%